Interferon gamma release assay post BCG among newborns and family members living in a crowded area in Jakarta, Indonesia - Francisca Srioetami Tanoerahardjo; Indri Rooslamiati; Natalie Kipuw; Hadiyanto; Soegianto Ali; Edhyana Sahiratmadja (Journal of Infection in Developing Countries)
Introduction: BCG vaccine is a mandatory for newborn in Indonesia, an endemic tuberculosis (TB) country that ranks second worldwide. A close contact with untreated active pulmonary TB individuals in a crowded area may result in TB disease or otherwise develop a latent TB infection (LTBI), as shown by positive result of interferon gamma release assay (IGRA).